SOCIAL ASPECT OF THE PHENOMENON OF BILINGUALISM IN INDIA - Bokuleva Б.С. (Journal of Oriental Studies, 2025)
Bilingualism is an effective way of communicating languages when a person uses two language systems at once. This article discusses the phenomenon of bilingualism in India, historical and cultural factors of its formation, types of bilingualism, place in society, social aspect. In the field of domestic Indian studies, the problem of Hindi-English bilingualism is being considered and studied for the first time. The purpose of the scientific article is to explain the bilingualism that arose as a result of language Relations, its types and features of Hindi – English bilingualism, conduct a survey among Indian bilinguists and analyze the results. This article is devoted to the study of its use among bilingual speakers in India in the social aspect. In the research work, the author used methods of sorting, generalization of scientific theoretical works, summarizing, conducting questionnaires and qualitative analysis of the results obtained, methods of SWOT analysis. The fields of application of Hindi and English among bilinguals in India have been identified and systematized. The results of the study can contribute to the study of the linguistic and psychological and social status of bilinguals, the study of the problem of bilingualism in Kazakhstan. The methodological basis and the results of the study can be used to study the phenomenon of bilingualism. Keywords: India, bilingualism, English, Hindi, language relations.